Performance evaluation of photolytic and electrochemical oxidation processes for enhanced degradation of food dyes laden wastewater - Sartaj, Seema; Ali, Nisar; Khan, Adnan; Malik, Sumeet; Bilal, Muhammad; Khan, Menhad; Ali, Nauman; Hussain, Sajjad; Khan, Hammad; Khan, Sabir [UNESP] (IWA Publishing, 2020)
Wastewater containing dyes is considered as the top-priority pollutant when discharged into the environment. Herein, we report for the applicability of 254 nm ultraviolet light and electrochemical process using a titanium ruthenium oxide anode for the degradation of Allura red and erythrosine dyes. During the photolytic process, 95% of Allura red dye (50 ppm) was removed after 1 h at pH 12 and 35 °C, whereas 90% color removal of erythrosine dye (50 ppm) was achieved after 6 h of treatment at pH 6.0 and 30 °C. On the other hand, 99.60% of Allura red dye (200 ppm) was removed within 5 min by the electrochemical process applying a current density (5 mA cmr2) at pH 5.0 and 0.1 mol L~1 sodium chloride (NaCl) electrolytic medium. Similarly, 99.61% of erythrosine dye (50 ppm) degradation was achieved after 10 min at a current density of 8 mA cmr2, pH 6.0, and 0.1 mol L~1 of NaCl electrolyte. The minimum energy consumption value for Allura red and erythrosine dyes (0.196 and 0.941 kWh m 3, respectively) was calculated at optimum current densities of 5 and 8 mA cmr2 The resultsdemonstrated that the electrochemical process is more efficient at removing dyes in a shorter time than the photolytic process since it generates powerful oxidants like the chlorine molecule, hypochlorous acid, and hypochlorite on the surface of the anode and initiates a chain reaction to oxidize the dyes molecules.
Keywords: Allura red; Electrochemical degradation; Environmental pollution; Erythrosine; Optimization; Photolysis